GENERIC PRODUCT DESIGN & VALIDATION METHODOLOGIES AT THE DETAILED DESIGN STAGE - Iorga Cristian; Desrochers Alain (European Scientific Journal, ESJ, 2013)
Doing design is to imagine and specify things that don’t exist, with the scope of modeling them and bringing them into the world. The «things» may be palpable-machines, buildings and bridges; they may be procedures-design methodologies for an organization or protocols for a manufacturing process, or for solving a scientific research problem by experiment; they also may be works of art-painting, lyrics, music or sculpture. Engineering design can be challenging and exciting, or it can be taxing, difficult and unproductive if the validation methods of the product are not linked to the client needs and to the product specifications. Uncertainties and variability always exist in design predictions. Loads are often variable and inaccurately known, strengths are variable and sometimes inaccurately known for certain failure modes or certain states of stress and other uncertainties may result from variations in the quality of manufacture, operation conditions or maintenance practices. One of the objectives of this paper is to outline a methodology that highlights the exciting challenges of product design and allows both engineers and students to focus on the development of a creative, effective and profitable solution. Another challenging goal of this paper would be to integrate design optimization and design validation at the detailed design phase in the product development process. Detailed design involves interactions between three elements: geometry, materials and loads. In this context, links between these elements will be formalized in terms of design methodologies. The optimization process allows finding one or more combinations of parameters maximizing or minimizing a given design criterion, while the validation activities provide feedback to the designers in order to verify the calculations accuracy and the achievement of all design criteria. To provide safe, reliable operation in the face of these variations and uncertainties, it is common practice to utilize the design safety factor and to integrate it into the product development process (PDP).